La lexicografia catalana actual - Cabré, M. Teresa (Caplletra. Revista Internacional de Filologia, 2015)
In this paper a general analysis of the evolution and current State of modem Catalan lexicography is undertaken, which starts with the setting up of a catalogue of lexicographic publications from 1940 onwards. In addition to the quantitative analysis of published dictionaries the paper introduces a typology study in order to sort out the variety and richness of modem Catalan lexicography. In the paper relevant data is presented on the situation of Catalan lexicography with respect to the quantity of existing dictionaries, and also on the factors that have determined their variety. Finally it can serve to establish the bases to build a lexicographic plan that helps to fill the gaps and avoids the unnecessary repetitions, so that Catalan can be given the same lexicographic resorts that are available for other widespread languages.